Alleviating Aspirin-Induced Gastric Injury by Binding Aspirin to β-Lactoglobulin - Chen J; Gong M; Huang Z; Wang F; Wang Y; Hu Z; Zeng Z; Wang Y (Dove Medical Press, 2022)
Jin Chen,1,* Min Gong,1,* Zhuo Huang,1 Fang Wang,2 Yajing Wang,3 Zuquan Hu,1 Zhu Zeng,1 Yun Wang2 1Key Laboratory of Biology and Medical Engineering/Immune Cells and Antibody Engineering Research Center of Guizhou Province, School of Biology and Engineering, Guizhou Medical University, Guiyang, 550025, People's Republic of China; 2Key Laboratory of Infectious Immune and Antibody Engineering of Guizhou Province, School of Basic Medical Sciences, Guizhou Medical University, Guiyang, 550025, People's Republic of China; 3The Affiliated Stomatological Hospital of Guizhou Medical University, Guizhou Medical University, Guiyang, 550025, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhu Zeng, Key Laboratory of Biology and Medical Engineering/Immune Cells and Antibody Engineering Research Center of Guizhou Province, School of Biology and Engineering, Guizhou Medical University, Guiyang, 550025, People's Republic of China, Email zengzhu@gmc.edu.cn Yun Wang, Key Laboratory of Infectious Immune and Antibody Engineering of Guizhou Province, School of Basic Medical Sciences, Guizhou Medical University, Guiyang, 550025, People's Republic of China, Tel/Fax +86851-88174044, Email wangyun@gmc.edu.cnPurpose: Gastric injury is a major issue for long-term administration of aspirin. In this work, we tried to explore the possibility of using BLG to alleviate aspirin-induced gastric injury, because of excellent abilities of BLG in loading drug molecules.Methods: Various spectroscopic techniques and molecular docking methods were applied to investigate the interaction mechanism between BLG and aspirin. Animal experiments were performed to figure out the effects of taking aspirin-BLG on the stomach.Results: Our results demonstrate that aspirin could bind with BLG to form stable aspirin-BLG complex (the binding constant Kb= 2.051 × 103 M− 1). The formation process is endothermic (∆H> 0) and the main acting force is hydrophobic force. Our data also show that the aspirin-BLG complex is formed with a higher affinity in simulated gastric fluid and could remain stable for several hours, which might arise from its special binding mode under acidic condition and the resistance of BLG to gastric digestion. Furthermore, animal models (rats with aspirin-induced gastric damage) were built. The results of animal experiments reveal that the oral administration of aspirin-BLG could cause less damage to gastric tissue, and it also hardly triggers obvious inflammatory responses.Conclusion: This study would contribute to an in-depth understanding of the interaction mechanism between BLG and aspirin. It is reasonable to believe that using BLG to bind with aspirin would be a potential way to alleviate the aspirin-induced gastric injury.Graphical Abstract: Keywords: beta-lactoglobulin, aspirin, gastric injury, static quenching, molecular docking